Tiwi signs huge barra farm deal - Smith, Camden.
tag=1 data=Tiwi signs huge barra farm deal tag=2 data=Smith, Camden tag=3 data=NT News tag=8 data=FISH%EMPLOYMENTVELOPMENT tag=9 data=TIWI LAND COUNCIL%SEA CAGE BARRAMUNDI FARM%PORT HURDTHURST ISLAND%PIVOT LIMITED%MELBOURNE tag=32 data=PALMER, MICK%PURUNTATAMERI, MARIUS%WATSON, JOHNMPBELL, BOB tag=34 data=PRSS tag=61 data=01 tag=62 data=Dec tag=63 data=1999